Making the next generation ACP agriculture work for women: Opening remarks by CTA s Director - Hailu, Michael (Technical Centre for Agricultural and Rural Cooperation, 2018)
In Africa, 68% of the economically active women are in agriculture, but they get very little part of that benefit. For example, in Cote d Ivoire, 68% of the labour in the cocoa sector come from women, but they only get 21% of the income. Therefore, there need to be interventions that make it easier for women to participate actively in the value chain and benefit from it.